A novel methodology for the angular position identification of the unbalance force on asymmetric rotors by response polar plot analysis. (October 2017) - Colín Ocampo, Jorge; Gutiérrez Wing, Enrique S.; Ramírez Moroyoqui, Félix J.; Abúndez Pliego, Arturo; Blanco Ortega, Andrés; Mayén, Jan
Highlights: A new methodology was developed in order to identify unbalance force angular position on asymmetric rotors. The proposed identifier was developed based on a two degrees of freedom simplified model of an asymmetric rotor. The proposed identifier was applied on experimental response polar plots obtained from an asymmetric Jeffcott type rotor. The proposed identifier shows itself as suitable tool for applying conventional balancing techniques on asymmetric rotors. The proposed identifier is fed with four points from rotor vibration response polar plot as input data. Abstract: It is well known that some mechanical systems, as a two pole generator, exhibit two different stiffness on the main inertial axis of its transverse section, which leads to complex vibration modes and complicates the determination of the angular position of the unbalance force and, consequently, the balancing process by conventional methods. Therefore, a methodology for the angular position identification of the unbalance force, based on a two-degrees-of-freedom mathematical simplified model of a rotor with unequal principal moments of inertia of the shaft transverse section, is proposed in this work. The methodology requires the analysis of the response polar plots of the rotor, as well as the information of the vibration response of at least four points from the response polar plot: vibration amplitude, phase angle and the angular velocity of the rotor. The identification of the unbalance force angular position was numerically and experimentally validated using the response polar plots experimentally acquired from a Jeffcott type rotor, which exhibits unequal principal moments of inertia of shaft transverse section and two inertial disks, which were analyzed for several unbalance force angular positions. The results showed slight differences between the identified and the experimental angular positions.